Implementation of the Teams Games Tournament Learning Model Assisted by Wordwalls in the Pancasila Education Subject for Grade IV - Dea Kanty Shahrina; Andriana Sofiarini; Tidi Maharani (EDUJAVARE: International Journal of Educational Research, 2026)
The process of developing potential is carried out through the process of education in an atmosphere and process towards students who are useful for themselves, society, and the state. This study aims to determine the completeness of learning outcomes of Pancasila education of fourth-grade students at SD Negeri 1 Kertosono after the implementation of the Teams Games Tournament (TGT) learning model assisted by wordwall. The subjects in this study were 22 fourth-grade students of SD Negeri 1 Kertosono, the technique in this study used a saturated sampling technique, namely all members of the population were sampled. Thus, all fourth-grade students of SD Negeri 1 Kertosono, as many as 22 students (13 boys and 9 girls), became the research sample. The method used in this study was an experiment with a pre-experimental design with one group pre-test and post-test categories. The research instrument was in the form of 14 multiple-choice questions whose validity had been tested. In the application of the wordwall game media, students were also formed into groups consisting of 5-6 students. Data analysis techniques used to calculate the average value, standard deviation, data normality test and hypothesis. Based on the calculation results obtained z count 8.51 and z table 1.64 with a = 5% (0.05). Because z count ≥ z table (8.51 ≥ 1.64), then Ho is rejected and Ha is accepted, meaning that the learning model of TGT assisted by word wall in Pancasila education subject of class IV of SD Negeri 1 Kertosono is significantly completed.